Lower-middle-class nation : the white-collar worker in British popular culture - Bishop, Nicola (New York, NY : Bloomsbury Academic, 2021)
"Lower-Middle-Class Nation provides an unparalleled interdisciplinary cultural history of the lower-middle-class worker in British life since 1850. Considering highbrow, lowbrow, and middle-brow forms across literature, film, television and more, Nicola Bishop traces the development of the lower-middle-class from the mid-19th century to the present day, tackling a number of pressing, consistent concerns such as automation, commuting, and the search for a life/work balance. Above all, this book brings together ideas about class, nationhood, and gender, demonstrating that a particularly British lower-middle-class identity is constructed through the spaces and practices of the everyday"--
Index en bibl.
Includes bibliographical references and index.
Keywords: Middle-class -- History -- Great Britain; Popular culture -- History -- Great Britain; Great Britain -- Social conditions